Cricothyroidotomy In Situ Simulation Curriculum (CRIC Study): Training Residents for Rare Procedures. Issue 2 (April 2017) - Petrosoniak, Andrew; Ryzynski, Agnes; Lebovic, Gerald; Woolfrey, Karen
Abstract : Introduction: Technical skill acquisition for rare procedures can be challenging given the few real-life training opportunities. In situ simulation (ISS), a training technique that takes place in the actual workplace, is a promising method to promote environmental fidelity for rare procedures. This study evaluated a simulation-based technical skill curriculum for cricothyroidotomy using deliberate practice, followed by an ISS evaluation session. Methods: Twenty emergency medicine residents participated in a two-part curriculum to improve cricothryoidotomy performance. A pretest established participant baseline technical skill. The training session consisted of two parts, didactic teaching followed by deliberate practice using a task-training manikin. A posttest consisted of an unannounced, high-fidelity ISS, during an emergency department shift. The primary outcome was the mean performance time between the pretest and posttest sessions. Skill performance was also evaluated using a checklist scale and global rating scale. Results: Cricothyroidotomy performance time improved significantly from pretest to posttest sessions (mean difference, 59 seconds; P < 0.0001). Both checklist and global rating scales improved significantly from the pretest to the posttest with a mean difference of 1.82 ( P = 0.002) and 6.87 ( P = 0.0025), respectively. Postcourse survey responses were favorable for both the overall curriculum experience and the unannounced ISS. Conclusions: This pilot study demonstrated that unannounced ISS is feasible and can be used to effectively measure cricothyroidotomy performance among EM residents. After a two-part training session consisting of didactic learning and deliberate practice, improved cricothyroidotomy skill performance was observed during an unannounced ISS in the emergency department. The integration of ISS in cricothyroidotomy training represents a promising approach; however, further study is needed to establish its role. Abstract : Supplemental digital content is available in the text.